2006
DOI: 10.1007/s00540-005-0358-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of propofol on ropivacaine metabolism in human liver microsomes

Abstract: A combination of the general anesthetic propofol and epidural anesthesia with a local anesthetic is widely used. The metabolism of ropivacaine and that of lidocaine are mediated by similar P450 isoforms. Previously, propofol was found to inhibit the metabolism of lidocaine in vitro. Here we investigated whether propofol inhibits the metabolism of ropivacaine using human liver microsomes in vitro. Ropivacaine (6.0 micromol.l(-1)) as the substrate and propofol (1-100 micromol.l(-1)) were reacted together using h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…However, side effects are inevitable and include irregular heart rate, low blood pressure, burning sensation at the site of injection and suppression of breathing (26). Combined application of epidural anesthesia, such as ropivacaine and lidocaine, may reduce the propofol doses required for the induction and maintenance of anesthesia, and further reduce its side effects in clinical practice (27,28). The present study investigated the effects of propofol and/or ropivacaine on cardiomyocytes in vitro under normoxic or CoCl 2 -induced hypoxic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, side effects are inevitable and include irregular heart rate, low blood pressure, burning sensation at the site of injection and suppression of breathing (26). Combined application of epidural anesthesia, such as ropivacaine and lidocaine, may reduce the propofol doses required for the induction and maintenance of anesthesia, and further reduce its side effects in clinical practice (27,28). The present study investigated the effects of propofol and/or ropivacaine on cardiomyocytes in vitro under normoxic or CoCl 2 -induced hypoxic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of propofol also induces strong suppression of CYP2C functions. In human liver microsomes, propofol can reduce CYP3A4 activity and then competitively inhibit ropivacaine metabolism [19]. Gemayel et al revealed the suppressive effects of propofol on hepatic CYP1A2 and CYP2B1 activities in their in vitro and in vivo studies [38].…”
Section: Discussionmentioning
confidence: 99%
“…For example, propofol was shown to decrease the clearance of midazolam and lidocaine possibly as a result of reducing hepatic CYP3A4 activity [17, 18]. In human CYP systems, propofol shows competitive inhibition to ropivacaine metabolism [19]. Our previous study exhibited that propofol possibly diminished kidney damage through suppressing renal CYP2E1 activity and enflurane metabolism to fluoride [20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…Those studies were conducted in vitro, and it is worth noting that in vivo factors such as absorption, distribution, protein binding and metabolism in organs other than the liver have a clinical influence on ropivacaine metabolism. Furthermore, it is not known whether the propofol inhibitory effect on ropivacaine metabolism is seen clinically (10,11).…”
mentioning
confidence: 99%